2021
DOI: 10.1097/prs.0000000000008312
|View full text |Cite
|
Sign up to set email alerts
|

A Matched Comparison of the Benefits of Breast Reduction on Health-Related Quality of Life

Abstract: A Matched Comparison of the Benefits of Breast Reduction on Health-Related Quality of Life Disclosure: Dr. Fischer has received payments as a consultant for Gore, Integra LifeSciences, Allergan, and Becton-Dickinson during the time of this study. The remaining authors do not have any financial disclosures to report. This research did not receive financial support for the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The results of our analysis demonstrate that overall, reduction mammoplasty affords improvements in all of the 4 primary QoL domains postoperatively when compared with preoperative scores. None of the individually selected studies indicated decreases in BREAST-Q scores after surgery, further substantiating the positive outcomes that patients consistently derive from this operation 26 . In addition, we highlight several associations between age, BMI, and individual preoperative and postoperative QoL measures.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…The results of our analysis demonstrate that overall, reduction mammoplasty affords improvements in all of the 4 primary QoL domains postoperatively when compared with preoperative scores. None of the individually selected studies indicated decreases in BREAST-Q scores after surgery, further substantiating the positive outcomes that patients consistently derive from this operation 26 . In addition, we highlight several associations between age, BMI, and individual preoperative and postoperative QoL measures.…”
Section: Discussionmentioning
confidence: 59%
“…None of the individually selected studies indicated decreases in BREAST-Q scores after surgery, further substantiating the positive outcomes that patients consistently derive from this operation. 26 In addition, we highlight several associations between age, BMI, and individual preoperative and postoperative QoL measures.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In this study, we merely tried to analyse the effect of our small but significant modification of preoperative markings on nipple height symmetry. Patient satisfaction after reduction mammoplasty is generally very high, [22][23][24][25] we do not dare to believe that our modification would make any significant difference. However, as plastic surgeons, we are committed to perfectionism and must perpetually try to improve even the smallest step towards the optimal result.…”
Section: Discussionmentioning
confidence: 92%